Monitoring the agri-food system in Myanmar: Rice millers – August 2022 survey round - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2022)
In August 2022, we surveyed 467 active rice millers from 13 states and regions across Myanmar to learn more about the impacts of the current political and COVID-19 crises. This report presents the key results and analysis from those interviews. Key findings  Electricity and fuel disruptions were cited as the most significant disruption by 91 percent of millers in August 2022. Rising fuel prices and access issues afflicted smaller, local mills while larger mills were more affected by interruptions in electricity supplies.  Continuing a trend from March 2022, banking and credit disruptions were less prevalent in August. Lending and borrowing show only minor changes relative to 2021.  Average milling throughput declined by more than 20 percent compared to a year prior, and stored volumes of both paddy and rice showed similar declines.  Rice prices and milling margins increased sharply by about 40 percent compared to last year, driven by rising global prices, and, most importantly, by a rapid devaluation of Myanmar kyat. In USD terms, the price increases are more modest and closer to global changes. At the parallel (unofficial) exchange rate, prices have declined.  Prices of byproducts (in kyats) have also increased sharply from the last year, especially for rice bran which is important to the animal feed industry. Looking forward  Looking forward to the 2022 monsoon harvest and marketing season, over half of all millers expect a decline in paddy production of at least 10 percent in their townships and an additional 22 percent of millers expect a smaller decline. Just 3 percent expect their local paddy production to be higher in 2022 monsoon than in 2021.  Changes in input use (e.g., a decline in fertilizer application) are far and away the most cited reason for lower expected paddy production. Half of millers said that less favorable rainfall patterns compared to 2021 are also a factor in lower paddy production.  On top of lower reported throughput in August 2022 and lower storage volumes, a decline in monsoon paddy production would have large implications for both rural and urban households. Lower supply coupled with the continued and widespread disruptions to utilities and transport, could drive prices even higher. At the same time, unpredictable foreign exchange and export policies could make it difficult for value chain actors to anticipate supply and demand conditions, resulting in higher price volatility.